2017
DOI: 10.1126/sciadv.aao1616
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, directed transport of DC-SIGN clusters in the plasma membrane

Abstract: Very rapid, directed movement of pathogen receptors in the plasma membrane is associated with MT close to the inner leaflet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 61 publications
(84 reference statements)
1
17
2
Order By: Relevance
“…In contrast to our model, Liu et al showed constitutive role of microtubule based retrograde transport of DC-SIGN nanoclusters to bring pathogens to the perinuclear region for antigen processing[21]. In this study, DC-SIGN nanoclusters were unladen with pathogen or attached to viral particles.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In contrast to our model, Liu et al showed constitutive role of microtubule based retrograde transport of DC-SIGN nanoclusters to bring pathogens to the perinuclear region for antigen processing[21]. In this study, DC-SIGN nanoclusters were unladen with pathogen or attached to viral particles.…”
Section: Discussioncontrasting
confidence: 69%
“…In resting cell membranes, the DC-SIGN tetramer self assembles into nanodomains, which have been described to undergo Brownian diffusion as well as apparent directed transport in some contexts [17][18][19]. For instance, DC-SIGN nanodomain tracking studies have reported that this receptor can undergo rapid, linear transport in the plane of the plasma membrane, suggesting that some directed mobility of DC-SIGN is possible [12,18,20,21]. As previously mentioned, directed transport at immunological contact sites (e.g., T cell or B cell synapses) often involves cytoskeleton/motor protein dependent centripetal motion of receptors toward the center of the contact site [10].…”
Section: Evidence For Active Transport Of Dc-sign Into the C Albicanmentioning
confidence: 99%
“…In resting cell membranes, the DC-SIGN tetramer self assembles into nanodomains, which have been described to undergo Brownian diffusion as well as apparent directed transport in some contexts [ 17 , 18 , 19 ]. For instance, DC-SIGN nanodomain tracking studies have reported that this receptor can undergo rapid, linear transport in the plane of the plasma membrane, suggesting that some directed mobility of DC-SIGN is possible [ 12 , 18 , 20 , 21 ]. As previously mentioned, directed transport at immunological contact sites (e.g., T cell or B cell synapses) often involves cytoskeleton/motor protein-dependent centripetal motion of receptors toward the center of the contact site [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The trajectories are then analysed, traditionally via mean squared displacement versus time plots (see below), to reveal the characteristics of the underlying motion. Using the SPT approach, it has been found that the diffusion behaviour of molecules in the cell membrane varies or regularly changes between multiple canonical patterns, namely free diffusion [30], confined diffusion [30], hop diffusion [31], channelled diffusion [32], stimulation-induced temporary arrest of lateral diffusion (STALL diffusion) [33] and directed motion [34]. The most common diffusion types seen are illustrated in Figure 2B.…”
Section: Single Particle Trackingmentioning
confidence: 99%